Systematic Evaluation of the Effects of Toxicant Exposure on Survival in Zebrafish Embryos and Larvae. Issue 9 (7th September 2021) - Ramdas Nair, Anjana; Delaney, Patrice; Koomson, Abigail Ama; Ranjan, Shashi; Sadler, Kirsten C.
Abstract: The use of whole animal models in toxicological studies is essential for understanding the physiological responses caused by chemical exposures. However, such studies can face reproducibility challenges due to unaccounted experimental parameters that can have a marked influence on toxicological outcomes. Zebrafish embryos and larvae are a popular vertebrate animal model for studying cellular, tissue, and organ responses to toxicant exposures. Despite the popularity of this system, standardized protocols that control for the influence of various experimental parameters and culture conditions on the toxicological response in these animals have not been widely adopted, making it difficult to compare findings from different laboratories. Here, we describe a detailed approach for designing and optimizing protocols to assess the impact of chemical exposures on the development and survival of zebrafish embryos and larvae. We first describe our standard procedure to determine two key toxicological thresholds, the maximum tolerable concentration (MTC) and the lethal concentration (LC50, defined as that in which 50% of larvae die), in response to an exposure that persists from early development through larval maturation. We then describe two protocols to systematically test how key experimental parameters, including genetic background, culture media, animal density, volume, plate material, and developmental stage in which the embryos are exposed, alter the MTC and LC50 . Finally, we provide a step‐by‐step guide to assess the interaction between two chemicals using this model. These protocols will guide the standardization of toxicological studies using zebrafish and maximize reproducibility. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Zebrafish embryo collection and culture, and establishment of the MTC and LC50 Basic Protocol 2 : Evaluation of the impact of culture conditions on toxicant responses of zebrafish embryo and larvae Basic Protocol 3 : Identification of the developmental window of sensitivity to toxicant exposure Basic Protocol 4 : Testing interaction between multiple toxicants